Impact of Autogenic Training on Anxiety in 14-15 Y.O. Racing Skiers before Competitions - N. Melentyeva, Natalia; L. Elagina, Natalia; V. Rumyantseva , Natalia (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the significance of psychological training of athletes, in particular, on the eve of competitions. It presents the characteristic and significance of athletes’ autogenic training. The research objective was to determine the efficiency of autogenic training impact on anxiety in 14- to 15-year-old racing skiers before competitions. The authors consider the importance of psychological training in the overall system of athletes’ training. Polling confirmed the topicality of this issue in the said age group. The level of personal and situational anxiety in 14-year-old racing skiers before competitions was determined. A complex of autogenic training was designed and evaluated for efficiency; practical recommendations were made. The research methods included: analysis of literature; psychodiagnosis; polling (questioning); and pedagogical experiment. The results of studying the level of personal and situational anxiety in adolescent racing skiers before competitions are presented, studied with the “Anxiety Research Test” by Ch. D. Spielberger. The polling results are described, confirming the presence of anxiety and stress before competitions. Based on the methods of autogenic training by I. G. Schultz, a complex of autogenic suggestions adapted for 14-year-old racing skiers was designed. The designed complex and the sequence of training are presented. The average score of personal anxiety in skiers before the experiment was 37, which is moderate according to Spielberger’s scale. The level of situational (before competitions) anxiety was 56, which is high. After the experiment, the average score of personal anxiety was 35 (moderate); the level of situational anxiety was 42 (moderate). The influence of autogenic training on anxiety level was analyzed by gender and sports qualification of athletes. The research confirmed the efficiency of autogenic training in achieving a stable psychological state in 14- to 15-year-old racing skiers before competitions.